2010
DOI: 10.1242/jcs.068619
|View full text |Cite
|
Sign up to set email alerts
|

Ca2+ chemotaxis inDictyostelium discoideum

Abstract: SummaryUsing a newly developed microfluidic chamber, we have demonstrated in vitro that Ca 2+ functions as a chemoattractant of aggregationcompetent Dictyostelium discoideum amoebae, that parallel spatial gradients of cAMP and Ca 2+ are more effective than either alone, and that cAMP functions as a stronger chemoattractant than Ca 2+ . Effective Ca 2+ gradients are extremely steep compared with effective cAMP gradients. This presents a paradox because there is no indication to date that steep Ca 2+ gradients a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
56
1

Year Published

2012
2012
2016
2016

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(68 citation statements)
references
References 96 publications
11
56
1
Order By: Relevance
“…Instead, we found that although iplA -cells undergo a normal chemokinetic surge in velocity in response to the increasing phase of each naturally relayed cAMP wave in wild-type aggregation territories, they lose the ability to reorient towards the aggregation center at the onset of the front of each wave. These results support a hypothesis, previously entertained (Scherer et al, 2010), that transient Ca 2+ gradients might be generated between cells at the onset of the front of each natural relayed cAMP wave that augment orientation towards the center of an aggregation territory, the source of each wave. If this hypothesis proves to be true, it would provide a more complex context for interpreting mutations that affect natural chemotaxis.…”
Section: Introductionsupporting
confidence: 89%
See 4 more Smart Citations
“…Instead, we found that although iplA -cells undergo a normal chemokinetic surge in velocity in response to the increasing phase of each naturally relayed cAMP wave in wild-type aggregation territories, they lose the ability to reorient towards the aggregation center at the onset of the front of each wave. These results support a hypothesis, previously entertained (Scherer et al, 2010), that transient Ca 2+ gradients might be generated between cells at the onset of the front of each natural relayed cAMP wave that augment orientation towards the center of an aggregation territory, the source of each wave. If this hypothesis proves to be true, it would provide a more complex context for interpreting mutations that affect natural chemotaxis.…”
Section: Introductionsupporting
confidence: 89%
“…mechanoreception) (Fache et al, 2005;Lombardi et al, 2008). Together, these results suggested that IplA was a strong candidate for a cell surface molecule or a molecule in the signal transduction pathway that mediated the facilitating effects of extracellular Ca 2+ on motility and cAMP chemotaxis, and/or Ca 2+ chemotaxis (Lusche et al, 2009;Scherer et al, 2010). Here, we provide evidence that IplA plays selective roles in the extracellular effects of Ca 2+ on cell behavior.…”
Section: Introductionmentioning
confidence: 58%
See 3 more Smart Citations